Understanding paratyphoid infection: study protocol for the development of a human model of Salmonella enterica serovar Paratyphi A challenge in healthy adult volunteers. Issue 6 (16th June 2015) - McCullagh, David; Dobinson, Hazel C; Darton, Thomas; Campbell, Danielle; Jones, Claire; Snape, Matthew; Stevens, Zoe; Plested, Emma; Voysey, Merryn; Kerridge, Simon; Martin, Laura B; Angus, Brian; et al.
Abstract : Introduction: This study will develop the first human challenge model of paratyphoid infection which may then be taken forward to evaluate paratyphoid vaccine candidates. Salmonella Paratyphi A is believed to cause a quarter of the estimated 20 million cases of enteric fever annually. Epidemiological evidence also suggests that an increasing proportion of the enteric fever burden is attributable to S . Paratyphi infection meriting further attention and interest in vaccine development. Assessment of paratyphoid vaccine efficacy in preclinical studies is complicated by the lack of a small animal model and the human-restricted nature of the infection. The use of experimental human infection in healthy volunteers provides an opportunity to address these problems in a cost-effective manner. Methods and analysis: Volunteers will ingest virulent S . Paratyphi A bacteria (NVGH308 strain) with a bicarbonate buffer solution to establish the infectious dose resulting in an 'attack rate' of 60–75%. Using an a priori decision-making algorithm, the challenge dose will be escalated or de-escalated to achieve the target attack rate, with the aim of reaching the study end point while exposing as few individuals as possible to infection. The attack rate will be determined by the proportion of paratyphoid infection in groups of 20 healthy adult volunteers, with infection being defined by one or more positive blood cultures (microbiological end point) and/or fever, defined as an oral temperature exceeding 38°C sustained for at least 12 h (clinical end point); 20–80 participants will be required. Challenge participants will start a 2-week course of an oral antibiotic on diagnosis of infection, or after 14 days follow-up. Ethics and dissemination: The strict eligibility criterion aims to minimise risk to participants and their close contacts. Ethical approval has been obtained. The results will be disseminated in a peer-reviewed journal and presented at international congresses. Trial registration number: NCT02100397.